RBTT-05. A SINGLE-ARM, OPEN-LABEL, PHASE II STUDY EVALUATING THE EFFICACY AND SAFETY OF ABEMACICLIB IN PATIENTS WITH RECURRENT OLIGODENDROGLIOMA: TRIALS IN PROGRESS. (11th November 2019) - Bagley, Stephen; Nasrallah, MacLean; O'Rourke, Donald; Hussain, Jasmin; Maloney-Wilensky, Eileen; Prior, Timothy; Brem, Steven; Desai, Arati
Abstract: BACKGROUND: Oligodendroglioma is a rare primary brain tumor characterized by mutation in the IDH1 / IDH2 genes and codeletion of chromosomes 1p and 19q. Although median overall survival extends beyond 10 years for patients with oligodendroglioma who receive adjuvant radiation and alkylating chemotherapy, the disease uniformly relapses and has no other effective treatments. The CIC gene, which encodes a high-mobility group box transcriptional repressor, is mutated in about 70% of oligodendrogliomas and is associated with worse prognosis and overexpression of cyclin D1 ( CCND1 ). Cyclin D1 assembles with the cyclin-dependent kinases CDK4 and CDK6 to cause phosphorylation of Rb protein and subsequent cell cycle progression from the G1 to S phase. Therapeutic inhibition of CDK4/6 activity, which leads to Rb dephosphorylation and cell cycle arrest, has revolutionized the care of breast cancer. The current phase 2 study will investigate the efficacy and safety of abemaciclib, a selective and potent small molecule inhibitor of CDK4 and CDK6 with significant brain-brain barrier penetration, in patients with 1p/19q codeleted oligodendroglioma that has recurred after standard radiation and alkylating chemotherapy. METHODS: This protocol (NCT03969706) has a single-arm, open-label, single-stage phase 2 design. Subjects will be treated with abemaciclib 200mg tablet twice daily on 28-day cycles until disease progression or unacceptable toxicity. Tumor response will be assessed according to modified Response Assessment in Neuro-Oncology (mRANO) criteria. The primary objective of the study is to determine the efficacy of abemaciclib for recurrent oligodendroglioma. The primary endpoint is the progression-free survival status of the subject at 6 months after enrollment (PFS-6). The alternative hypothesis is that the proportion of subjects without an event at 6 months will be ³85%. We will test this hypothesis against a null hypothesis of PFS-6 = 50%. With enrollment of 10 planned subjects, the power to detect this difference is 82% (one-sided alpha = 0.05).